PASANG SURUT PERAN POLITIK MASYUMI DALAM PEMERINTAHAN (1945-1960) - Siregar, Insan Fahmi (Faculty of Social Science, Universitas Negeri Semarang, 2008)
Masyumi Party (Partai Majelis Syuro Muslimin Indonesia) was a major Islamic political party inIndonesia. It was originally established by the occupying Japanese in 1943 in an attempt to control Islam inIndonesia. In 1952, Nahdlatul Ulama seceded from Masyumi and create the new party, based on traditionalsociety. The party came second in the 1955 election with 20.9% of the popular vote. During the period ofliberal democracy era, Masyumi members had seats in parliament and the party supplied prime ministerssuch as Muhammad Natsir and Burhanuddin Harahap. The group’s leaders campaigned for an Islamicstate in the 1950’s not out of a real conviction, but mainly from fear of being outflanked by the largerand more aggressive Masyumi. Under the dictatorships, the group withdrew from partisan politics, butwith the restoration of democracy it formed a new party, National Awakening, open to all religions andcommitted to a secular state. In 1958, some Masyumi members joined the PRRI rebellion against Sukarno.Two years later in 1960, Sukarno banned Masyumi and Socialist Party, and sent Masyumi leaders to jail.Keywords: Masyumi Party, opposes, democracy, government